Looking Back - Brenner, Y. S. (Journal of Income Distribution®, 1998)
This contribution looks back at the ideas I have held and elaborated on during the years I worked at Utrecht University. An important theme concerns the explanation of the mechanisms by which the national income is distributed between groups and individuals in the economy. I believe that the restoration of the humane ideals of the founders of the Welfare State is more important that the present opportunism, placing more trust in rhetoric than in truth. A maladie of economists is to flex with the fashion of the time, and try to find remedies for the symptoms of the malaise that plagues the Welfare State, by monetary measures to contain inflation and to cut back government expenditure, to be paving the way into a social, economic and moral morass. A revival of the public’s political engagement, and a revision of economic theory is necessary.